Erratum: The Transient Outgassed Atmosphere of 55 Cancri e (2023, ApJL, 956, L20) - Kevin Heng (The Astrophysical Journal Letters, 2024)
Due to a coding error, the top left panel of Figure 2 is in error. Consequently, tens of bars of carbon monoxide and carbon dioxide are required to render an atmosphere optically thick to Rayleigh scattering. However, this error does not propagate into the calculation of the eclipse depths. The key conclusions of the study remain unchanged.